Pengaruh Pendapatan, Pengetahuan Dan Kualitas Pelayanan Terhadap Minat Nasabah Menabungan Emas Di Unit Pegadaian Syariah UIN STS Jambi - Indah Apriani; Nazori Majid; Rohana Rohana (Universitas 17 Agustus 1945 Semarang, 2023)
Gold Savings is a gold balance deposit service that makes it easier for people to invest in gold savings. Gold savings are one type of investment that is in great demand by the public. This study aims to determine whether or not there is an effect of income, knowledge and quality of service on customer interest in saving gold. This research method is quantitative with multiple linear regression analysis as the analysis tool. The population in this study was 336 respondents, the sample was determined using the slovin formula, the sample in this study was 77 respondents and this research was conducted on customers of the Sharia Pawnshop Unit of UIN Sulthan Thaha Saifuddin Jambi. The results of this study indicate that the results of the F-test of income, knowledge and service quality variables together have a significant effect on customer interest in saving gold, by t-test income does not significantly affect customer interest in saving gold, knowledge has a significant effect on customer interest. saving gold and service quality significantly influence customer interest in saving gold.